Isotopic Evidence of a Wide Spectrum of Feeding Strategies in Southern Hemisphere Humpback Whale Baleen Records - Eisenmann, Pascale; Fry, Brian; Holyoake, Carly; Coughran, Douglas; Nicol, Steve; Bengtson Nash, Susan (PLOS ONE, 2016)
Our current understanding of Southern hemisphere humpback whale (Megaptera novaeangliae) ecology assumes high-fidelity feeding on Antarctic krill in Antarctic waters during summer, followed by fasting during their annual migration to and from equatorial breeding grounds. An increase in the number of reported departures from this feeding/fasting model suggests that the current model may be oversimplified or, alternatively, undergoing contemporary change. Information about the feeding and fasting cycles of the two Australian breeding populations of humpback whales were obtained through stable isotope analysis of baleen plates from stranded adult individuals. Comparison of isotope profiles showed that individuals from the West Australian breeding population strongly adhered to the classical feeding model. By contrast, East Australian population individuals demonstrated greater heterogeneity in their feeding. On a spectrum from exclusive Antarctic feeding to exclusive feeding in temperate waters, three different strategies were assigned and discussed: classical feeders, supplemental feeders, and temperate zone feeders. Diversity in the inter-annual feeding strategies of humpback whales demonstrates the feeding plasticity of the species, but could also be indicative of changing dynamics within the Antarctic sea-ice ecosystem. This study presents the first investigation of trophodynamics in Southern hemisphere humpback whales derived from baleen plates, and further provides the first estimates of baleen plate elongation rates in the species.